ANALISIS KINETIKA PENDUGAAN UMUR SIMPAN BENIH CABAI MERAH - Elisa Julianti, Soewarno T.Soekarto , Purwiyatno Hariyadi dan Atjeng M.Syarief (Department of Agroindustrial Technology, Bogor Agricultural University, 2005)
ABSTRACTModification of the Asni’s mathematical model was adopted to predict the shelf life of red chilli seeds, based on the first order of kinetics in the deterioration process of seed viability. Application of the modified model to storage experiments of red chilli seeds at different moisture contents of 14.3 % and above, the shelf life of the seeds was only one month or less, at moisture contents of 6.5 to 10.6 % was 4 to 26 months, while at very low moisture contents was more than 26 months. From this research it was found that the safe moisture content in room temperature storage of red chilli seeds required moisture content in the region of secondary bound water (between 4.0 – 12 % wet basis). For very long shelf life the seeds could be stored in the region of primary bound water ( bellow 4.0 % moisture), but along with the risk of hard seed phenomenon. Key words : Seeds, Red Chilli, Shelf Life, Storage, Mathematical Model